A fuzzy logic-based risk evaluation and precaution level estimation of explosive, flammable, and toxic chemicals for preventing damages - Abdul Aziz; Md Masum Suzon; Rakib Hasan (Heliyon)
Chemical industries are highly vulnerable to accidental events or terrorist attacks due to their processing, storage, and transportation of explosive, flammable, and toxic materials. Major industrial risks include fire, explosion, and toxic chemical release. An effective risk evaluation system is essential to prevent accidents or terrorist attacks. The proposed system can evaluate the risk of handling hazardous chemicals and determine the appropriate precaution level to prevent accidents using a fuzzy inference system. The inventory size, explosiveness, flammability, and toxicity of the chemicals are used as input variables for evaluating the output variable risk. The defuzzified value of risk indicates the amount of damage it can cause if accidents happen. Using the calculated risk value and the location of the chemical industry as input variables, precaution level can be determined. Security arrangements have been recommended based on the different precaution levels so that industries can take appropriate measures according to the calculated results. This approach helps to protect the environment and save lives from any mishaps.